Pioneers of modern China : understanding the inscrutable Chinese - Lee, Khoon Choy, 1924- (World Scientific Pub., 2005)
Amongst the Chinese exists great cultural variety and diversity. The Cantonese care more for profit than face and are good businessmen, whereas Fujian Rén are frank, blunt and outspoken but daring and generous. Beijing Rén are more aristocratic and well-mannered, having stayed in a city ruled by emperors of different dynasties. Shanghai Rén are more enterprising, adventurous and materialistic but less aristocratic, having been at the center of pre-war gangsterism. Hainan Rén are straightforward, blunt and stubborn. Hunan Rén are more warlike and have produced more marshals and generals than an.